Characterization and Storage Stability Study of Guava and Mango Wood Smoked Induced Spiced Cultured Milk (Raita) - Chaudhuri, Arghya; Aditya; Mishra, Himanshu; Patidar, Sachin; Rehman, Hameedur; Choudhary, Lokesh; Kumar, CTM (Journal of Food Technology Research, 2022)
A study was conducted to evaluate the effect of the smoking of raita with guava and mango wood on its functional properties and storage stability. The raita was smoked with guava and mango wood for 2.5, 5, 7.5, and 10 min in a closed chamber. The smoked raita was evaluated for change in titratable acidity (TA), pH, total phenolic content (TPC), antioxidant activity (DPPH), colour (L*, a*, and b*), and sensory attributes. Both guava and mango wood smoked samples didn’t show significant changes (P<0.05) in TA, pH, TPC, and antioxidant activity. All colour values (L*, a* and b*) of smoked samples were significantly (P<0.05) higher than the control sample, particularly, the yellowish attribute (b*) was very high in smoked samples. The sample that smoked for 7.5 min had very high overall acceptability scores in both kinds of wood and which is considered as an optimum smoking time for raita. The selected raita samples were stored for 9 days at 4°C and assessed for TA, pH, and standard plate count (SPC) at 3 days of interval. During the storage period, a significant reduction (P<0.05) in pH and a significant increase (P<0.05) in TA was seen till the 6th day of storage. The smoked samples had considerably lower SPC than the control sample and SPC was decreased significantly (P<0.05) with an increase in storage days in all the samples. The preparation is simple and can be served in Pubs/Bars, Casual Dining Restaurants & QSRs (Quick served restaurants).